Optimality to Flow and Design of Double T-shape Branching Ducts with Newtonian Fluid and Impermeable Wall - Pepe, V. (2020)
In this work Constructal Design is used to maximize the flow access in two levels of T shaped bifurcation ducts. The aim is to find the flow resistance, under size constraints, in three-dimensional (3D) networks with different homothetic relationships between sizes (diameters and lengths) of parent and daughter ducts. T-junction having parent-to daughter size ratios ranging from 0.5 to 1.5 were studied, under laminar flow (Reynolds numbers equal to 102). The main outcomes of this study are to investigate the flow features within the network, and to compare the homothetic relationships between sizes obtained with analytical relations available in the literature.